Now that we have a free float... / ВОТ И ПУСТИЛСЯ КУРС В ПЛАВАНИЕ… - Jochec (Йохец), Marek (Марек) (National Business KZ, 2015)
On tenge devaluation and switch to free float regime.
Keywords: tenge; free float; exchange rate; devaluation; currency risk